Advantages of the polysaccharides from Gracilaria lemaneiformis over metformin in antidiabetic effects on streptozotocin-induced diabetic mice. Issue 15 (30th January 2017) - Wen, Lingrong; Zhang, Yunlin; Sun-Waterhouse, Dongxiao; You, Lijun; Fu, Xiong
Abstract : In the present study, polysaccharides from Gracilaria lemaneiformis (GLP) were obtained by citric acid extraction, and had a low molecular weight (21.2 kDa) with a high amount of galactose. Abstract : In the present study, polysaccharides from Gracilaria lemaneiformis (GLP) were obtained by citric acid extraction, and had a low molecular weight (21.2 kDa) with a high amount of galactose. GLP showed effective inhibitory effects on α-amylase activity. After a six-week animal trial, GLP was found to combat streptozotocin (STZ)-induced diabetes and associated with oxidative stress, via its regulation of glucose and lipid metabolism, repair of pancreatic β-cells, protection of liver and kidney function, promotion of the activities of endogenous antioxidant enzymes, and suppression of lipid peroxidation. A dose-dependent manner was found in these examinations except for the glucokinase level, superoxide dismutase activity, and malondialdehyde content. GLP treatments were also more effective at regulating the insulin level, lipidemic parameters and blood urea nitrogen level than metformin treatment. Thus, GLP is more advantageous than metformin not only in the naturalness of GLP but also in the action of combating STZ-induced diabetes. Accordingly, GLP may be utilized as a potential functional food supplement for diabetes prevention in the future.